2020
DOI: 10.1186/s42523-020-00025-9
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis suggests broad metabolic potential in extracellular symbionts of the bivalve Thyasira cf. gouldi

Abstract: Background: Next-generation sequencing has opened new avenues for studying metabolic capabilities of bacteria that cannot be cultured. Here, we provide a metagenomic description of chemoautotrophic gammaproteobacterial symbionts associated with Thyasira cf. gouldi, a sediment-dwelling bivalve from the family Thyasiridae. Thyasirid symbionts differ from those of other bivalves by being extracellular, and recent work suggests that they are capable of living freely in the environment. Results: Thyasira cf. gouldi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Symbiont-hosting and symbiont-free individuals of one particular thyasirid species are found cooccurring in nature, which shows that this association is likely an optional nutritional supplement, rather than essential for survival ( 4 6 ). The symbionts have estimated genome sizes typical of their closest free-living relatives and can probably survive in a free-living form in the environment ( 7 ). Most chemosynthetic symbioses are horizontally transmitted, meaning they are acquired from the environment or from cooccurring hosts during development ( 8 ).…”
Section: Defining Chemosynthetic Symbiosesmentioning
confidence: 99%
“…Symbiont-hosting and symbiont-free individuals of one particular thyasirid species are found cooccurring in nature, which shows that this association is likely an optional nutritional supplement, rather than essential for survival ( 4 6 ). The symbionts have estimated genome sizes typical of their closest free-living relatives and can probably survive in a free-living form in the environment ( 7 ). Most chemosynthetic symbioses are horizontally transmitted, meaning they are acquired from the environment or from cooccurring hosts during development ( 8 ).…”
Section: Defining Chemosynthetic Symbiosesmentioning
confidence: 99%
“…Endosymbionts housed in deep-sea mussels and tubeworms have a transport system to take up various carbohydrates (Robidart et al, 2008;Ho et al, 2017;McCuaig et al, 2018). On the contrary, the endosymbionts of the deep-sea vesicomyid clams reportedly lacked the genes related to the systems for absorbing phosphoenolpyruvate-dependent sugar in the genomes (Kuwahara et al, 2007).…”
Section: Complementary Roles Of the Two Partners In The Holobiontmentioning
confidence: 99%
“…Thyasira cf. gouldii symbiont is observed as type 2, which is classified into the genus Sedimenticola (family Sedimenticolaceae) based on 16S rRNA gene sequence (McCuaig et al, 2020). The newly released output about C. bisecta clearly demonstrated that these symbionts were aggregated in the apical vesicles (type 3) and might have pathways connecting to environment (Guo et al, 2023), which is consistent with the earlier identification (a more advanced state) by Dufour (2005).…”
Section: Resultsmentioning
confidence: 99%
“…Thyasira cf. gouldii and Conchocele bisecta ) with the metabolic potentials of the host/symbiont have been studied using the metagenomic approach (Guo et al, 2023; McCuaig et al, 2020). There are only 15 bacterial 16S rRNA gene sequences from the potential thyasirid symbionts on GenBank (last access Jan 2023) and one metagenome‐assembled genome of C. bisecta symbiont (Guo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%